CONFLICT AND DELAY IN CONSTRUCTION PROJECTS: A SYSTEMATIC LITERATURE REVIEW - Abu Hasan, Abdul; Fenn, Peter; Aminian, Elika (Journal of Engineering and Technology (JET), 2025)
This study conducts a systematic literature review (SLR) of 90 publications from 2007 to 2024 on the link between conflict and delay in construction projects. Conflicts are categorized as behavioral, contractual, and technical, with 93 common conflict factors identified across project phases. The research highlights the importance of early issue identification and phase-specific strategies to reduce delays, emphasizing the need for effective project management, clear contracts, and thorough design. A qualitative methodology, involving semi-structured interviews with 18 construction professionals, explores stakeholders’ perspective. Thematic analysis, supported by NVivo software, led to a model illustrating the conflict-delay relationship.